Isolation, purification and characterization of vinblastine and vincristine from endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Patil, Deepak; Rajamohanan, Pattuparambil Ramanpillai; Ahmad, Absar (Plos One, 2013)
Endophytic fungi reside in a symbiotic fashion inside their host plants, mimic their chemistry and interestingly, produce the same natural products as their hosts and are thus being screened for the production of valuable compounds like taxol, camptothecin, podophyllotoxin, etc. Vinblastine and vincristine are excellent anti-cancer drugs but their current production using plants is non-abundant and expensive. In order to make these drugs readily available to the patients at affordable prices, we isolated the endophytic fungi from Catharanthus roseus plant and found a fungus AA-CRL-6 which produces vinblastine and vincristine in appreciable amounts. These drugs were purified by TLC and HPLC and characterized using UV-Vis spectroscopy, ESI-MS, MS/MS and H-1 NMR. One liter of culture filtrate yielded 76 mu g and 67 mu g of vinblastine and vincristine respectively. This endophytic fungal strain was identified as Fusarium oxysporum based upon its cultural and morphological characteristics and internal transcribed spacer (ITS) sequence analysis.

Investigation of domain structures in monomethoxy poly(ethylene glycol)-b-poly(caprolactone) grafted poly(acrylic acid) by NMR diffusion studies - Tiwari, Neha; Badiger, Manohar Virupax; Rajamohanan, Pattuparambil Ramanpillai; Ravindranathan, Sapna (Polymer International, 2022)
Associating polymers developed by grafting a block copolymer of monomethoxy poly(ethylene glycol)-b-poly(caprolactone) (MPEG-b-PCL) onto poly(acrylic acid) undergo an irreversible sol-gel transition on heating. The influence of various physicochemical parameters on the thermoresponsive behaviour was examined by rheology and NMR studies. Pulsed field gradient NMR diffusion studies were performed to probe the mechanism of thermally induced gelation. Analysis of the diffusion data reveals the presence of loosely and strongly associated structures which respond differently to variation in temperature. It is observed that the polymer solution, which is visibly homogeneous, is heterogeneous on a mesoscopic scale with a distribution of domains. Detailed investigation of the thermally induced sol-gel transition shows that the mechanism of gelation involves irreversible alterations in the domain structure and size. (c) 2022 Society of Industrial Chemistry.
Keywords: associating polymers; hydrophobically modified polymers; NMR diffusion studies; Rheology; sol-gel transition; thermoresponsive polymers